Inflammatory fibroid polyp of the stomach mimics malignancy on F-18 FDG PET/CT imaging - Bilgin, Sabriye Şennur; Bilgin, Mehmet; Savaş, Recep; Erdoğan, Ezgi Başak (Lippincott Williams & Wilkins, 2016)
Inflammatory fibroid polyps (IFPs) are rare non-neoplastic and proliferating submucosal lesions of the gastrointestinal tract. The classic IFP, which was first described by Vanek, consists of prominent blood vessels and is characterized by a heavy inflammatory infiltrate, which is rich in eosinophilic granulocytes. The clinical presentation depends on the size and location. Inflammatory fibroid polyps cannot be differentiated from malignancy without histological examination. We report a case of IFP in the stomach that mimicked a primary gastric malignancy showing an increased F-18-FDG uptake.
WOS: 000381315000024
PubMed ID: 27454603
Keywords: inflammatory Fibroid Polyp; Vanek's Polyp; F-18-FDG PET/CT